Draft Genome Sequence of Pantoea ananatis B1-9, a Nonpathogenic Plant Growth-Promoting Bacterium - Kim, Hyun Jung (American Society for Microbiology, 2012)
Pantoea ananatis B1-9 is an endophytic Gram-negative rhizobacterium that was isolated for its ability to promote plant growth and improve crop yield in the field. Here we report the draft genome sequence of P. ananatis B1-9. Comparison of this sequence to the sequenced genome of a plant-pathogenic P. ananatis strain, LMG20103, indicated that the pathogenesis-related genes were absent, but a subset of gene functions that may be related to its plant growth promotion were present.